IgG4 Status in Explanted Livers Does Not Affect the Outcome of Primary Sclerosing Cholangitis (PSC) After Liver Transplant - Al-Judaibi, Bandar; Hernandez-Alejandro, Roberto; Herath, Chaturika; Chakrabarti, Subrata; Dokus, M. Katherine; Marotta, Paul; Alghanem, Mansour (Hepatitis monthly, 2018)
Background: The outcome of primary sclerosing cholangitis (PSC) after liver transplantation can be affected by recurrent PSC (rPSC) and subsequent graft failure. IgG4-related sclerosing disease is a recently described entity that has a similar morphological appearance to PSC, making the distinction difficult. However, IgG4-related sclerosing cholangitis has an excellent prognosis since it is steroid sensitive, but the impact of IgG4 on rPSC after liver transplant is still unknown. Objectives: To determine the association between IgG4 positive immunochemical staining in liver explants and recurrence of primary sclerosing cholangitis post-liver transplantation. Methods: Clinical information on all adult patients who underwent liver transplantation for PSC from 1990 to 2014 at our institution was obtained. IgG4 immunochemical staining was performed on the porta-hepatis region of these patient’s explanted livers. Immunochemical staining was considered to be positive if the score was > 5 cells/high power field (HPF). Results: Eighty patients met inclusion criteria. IgG4 staining was positive in 21 subjects. Median time for follow-up in the IgG4 positive group was 99.6 months compared to 152.6 months in the IgG4 negative. There were more instances of rPSC in the IgG4 negative group compared to the IgG4 positive group (26% vs. 5%, P < 0.009), and rPSC occurred earlier in the IgG4 negative group (P = 0.016). The frequency of graft failure, however was not significantly different among the two groups. Conclusions: The presence of IgG4 positive cells in liver explants of patient’s transplanted for PSC is associated with fewer episodes of and longer time to recurrent PSC. In addition, IgG4 status of the liver explants does not affect graft survival. Presence of IgG4 positive cells may suggest protective effect against recurrence of PSC.